The Effect of Supervision and Awareness of Taxpayers on Increasing Regional Tax Revenue and Its Impact on Taxpayer Compliance - Helen Susanto; Weti Kurniawati; Wawat Hermawati (PT. Berkah Digital Teknologi, 2022)
Purpose of the study — The purpose of this study was to measure the effect of supervision and awareness of taxpayers on increasing local tax revenues and their impact on taxpayer compliance in the West Region Tax UPTD, Cirebon Regency Regional Revenue Management Agency.Research method— This study uses a quantitative approach to the variables of supervision and awareness of taxpayers, while the research instrument is in the form of a questionnaire with a path analysis approachResult— The results obtained: 1) simultaneously supervision and awareness of taxpayers, 2) partially: supervision, and 3) taxpayer awareness has a significant effect on increasing local tax revenues, 4) direct supervision has a significant effect on taxpayer compliance by (0.259) 2 X 100% = 0.010, meaning that the level of taxpayer compliance is not influenced by supervision of 0.010 while the remaining 0.090 is influenced by other factors. The direct effect of taxpayer awareness on taxpayer compliance is (0.786)2 X 100% = 0.617, meaning that the level of taxpayer compliance is influenced by taxpayer awareness of 0.083, the remaining 32.3% is influenced by other factors, 5) directly increases tax revenue area has a significant effect on taxpayer compliance by (0.144)2 X 100% = 0.020, meaning that the level of taxpayer compliance is influenced by an increase in local tax revenue of 0.020 or 20% while the remaining 80% is influenced by other factors.Conclusion— Taxpayers need to be aware of their obligations in paying taxes by understanding the taxes paid for the purposes of community and state development. Because so far knowledge of the allocation of taxes paid is considered not right on target, so there needs to be better socialization.